MALNUTRITION RISK FACTORS BASED ON SLEEP DURATION AND PHYSICAL ACTIVITY: STUDIES IN BANGLADESH AND INDONESIA - Catur Wulandari; Anugrah Linda Mutiarani; Pratiwi Hariyani Putri; Sa’bania Hari Raharjeng (The Indonesian Journal of Public Health, 2026)
Introduction: Indonesia faces a "double burden" of malnutrition, particularly among vulnerable adolescents. While 16.8% are underweight, a combined 26.8% are overweight or obese. Modern malnutrition, driven by shifts in diet and physical activity, has evolved from simple nutrient deficiencies to include widespread overnutrition. Aim: This study aimed to assess the characteristics of adolescents in Indonesia and Bangladesh, the prevalence of malnutrition, and factors associated with malnutrition among adolescents in Indonesia and Bangladesh, including physical activity and sleep duration. Methods: The research design employed analytic observations with a cross-sectional approach. The sample comprosed 108 high school adolescents in Indonesia and 108 in Bangladesh. Respondents were selected using simple random sampling. Data were analyzed using a Spearman statistical test with a significance level of α = 0.05. Result: The biggest nutritional problem found among adolescents in Indonesia was obesity at 22.2%, with less sleep duration at 59.3% and a moderate level of physical activity at 69.4%. Meanwhile, in Bangladesh, the biggest nutritional problem found was underweight at 33.3%, with adequate sleep duration at 95.61% and sufficient physical activity at 52.7%. There was a significant correlation between sleep duration and nutritional status (p<0.001). Physical activity was not significantly correlated with nutritional status (p = 0.797). Conclusion: The relationship between sleep duration and nutritional status has a negative direction, indicating that shorter duration is associated with lower nutritional status. Health policies should integrate education on the prevention of nutrition problems ini adolescents into school-based nutrition programs, wich include physical activity and sleep duration.